Perceived Stress and Associated Factors among Adults residing in a Rural Community of Nepal: A Community-based Study - Sharma, Muna; Singh, Babita; Adhikari, Bibhav (Journal of Institute of Medicine Nepal, 2025)
Introduction Stress contribute to disorganized working capacity of adult’s life that leads to various comorbidity. The burden like stress-related common mental disorders are on the rise in Nepal. The aim of the study was to estimate stress level and its associated factors among adults. Methods A community based, Cross-sectional survey was done among 600 adults aged >18 years, residing in Prasauni Rural Municipality, Nepal. Respondents were interviewed in local language using WHO STEPs questionnaire and prevalence of stress was determined by using perceived stress scale. The data was analyzed using IBM SPSS version 20. Odds ratio was calculated to identify the independent predictors of the outcome variable. Results Almost equal portion of the participants were male (47.7%) and female (52.3%). and most of them were of age less than 35 years. Regarding the level of stress, 508 (85.2%) respondents were having low level and 88(14.8%) respondents were having moderate level of stress. Respondents’ age was associated with perceived stress level(p<0.05). Poor sleep quality tends to increase stress 4 times more (OR 4.04, CI 2.257-7.25). Although not significant, tobacco use, physical inactivity, tobacco and alcohol use, and increased blood pressure had higher odds for stress level. Conclusion Stress symptoms are prevalent in low to moderate level among adults of rural community in Nepal. Poor sleep quality is a significant predictor of increase stress level. Further exploratory investigations are needed.